Efektifitas Kebijakan Operasi Ketupat Semeru 2021 dalam Mengendalikan Penularan Covid-19 di Kabupaten Sidoarjo - Fidianing Sopah; Lukman Arif (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to analyze the effectiveness of the 2021 Ketupat Semeru Operational Policy in  the of Covid-19. The problem is focused on the results of the policy operation that has been carried out by the Indonesian National Police with the code "Ketupat Jaya 2021" in Sidoarjo Regency, it is found that there is still a spike in psitive cases of Covid-19. To approach this problem, Sutrisno's 2017 effectiveness theory reference is used with five focuses, namely understanding the program, being on target, being on time, achieving goals, and real change. The data were collected through interviews, observation, documentation and others, and analyzed descriptively qualitatively. This study concludes that the 2021 Ketupat Semeru Operational Policy in Sidoarjo Regency is considered not yet effective in dealing with Covid-19 transmission.